Do the expressions about customarily doing reflect our cognition and emotion: evidence from Chinese BCC corpus - Zhang, Limin; Lv, Zhaojie; Ren, Longbo (Frontiers in Psychology, 2025)
Through an in-depth analysis of the Chinese BCC colloquial corpus, this paper discusses the cognitive and emotional features of the temporal contouring of “customarily X” (X refers to verb or adjective) in spoken Chinese, focusing on the two different expressions of “often V” (V= verb) and “be often A” (A= adjective). Data analysis indicates that the “often V” structure is primarily used to express the frequent occurrence of actions, and its collocation with bounded verbs not only signifies the repetition of actions but also indexes the repetition of time on the timeline. The “often + unbounded verbs” changes the state of unbounded verbs and activates bounded cognitive processing. The “be often A” structure typically describes the regularity of emotions and physical sensations, and its frequent co-occurrence with negative adjectives serves to manifest the mental time of human cognition. These findings enrich the empirical basis for the study of temporal contouring in spoken Chinese and provide a nuanced analytical perspective for investigating the interface between cognitive mechanisms and affective dimensions in colloquial discourse.